Gilligan's Island. The complete third season [videorecording (DVD)] - Schwartz, Sherwood; Denver, Bob; Hale, Alan, 1918-1990; Backus, Jim; Schafer, Natalie, 1900-1991; Tina Louise, 1934-; Johnson, Russell, 1924-2014; Wells, Dawn, 1938-2020 (Turner Entertainment Co., 2011)
Follows the comic adventures of seven castaways stranded on a South Pacific island.